Topical Ophthalmic Atropine in Horses – An Experimental Study. (September 2014) - Ström, L.; Dalin, F.; Domberg, M.; Haubro Andersen, P.; Ekesten, B.
Abstract : Reasons for performing study: Topical administration of atropine is an important part of the treatment of equine uveitis. However, very high doses of topically administered atropine have been associated with decreased gut motility and colic in horses. Objectives: To evaluate systemic effects of topical atropine in doses used clinically in horses, with emphasis on gut motility and ability to induce colic. Study design: Randomised, blinded, controlled crossover study. Methods: Four horses received placebo eye drops (saline) and 2 different protocols of topical atropine administration during 120 h with 35 days washout periods in between different treatments. One drop of 1% atropine solution was administered unilaterally at 3‐h intervals for 48 h and at 12‐h intervals for another 72 h (high dose), whereas the low dose group was given alternating treatment with atropine and saline according to the same protocol. In the placebo group, saline was administered at 3‐h intervals for 48 h and at 12‐h intervals for another 72 h. All horses were walked for 10 min 3 times a day. Pupillary light reflexes, heart rate, respiratory rate, gut sounds and clinical signs of abdominal pain were monitored every 3 h and faecal output once daily. Results: None of the horses showed any signs of abdominal pain. Gut sounds were present at every auscultation in all horses. Gut sound scores were significantly lower during the high dose regime (P = 0.0007) compared to placebo, but not during the low dose regime (P = 0.17). Conclusions: Topically administered atropine in clinically relevant doses temporarily reduced gut motility, but did not cause ileus or colic in healthy horses receiving a small amount of daily exercise. However, this effect may be additive to other factors that reduce gut motility in horses with uveitis, such as pain and stress in relation to hospitalisation. Ethical animal research: The regional Ethical Committee (Uppsala Djurförsöksetiska nämnd, Sweden, Dnr C372/12) approved the use of the horses in this study.Sources of funding: None.Competing interests: None.